Pengaruh Pengetahuan, Kompetensi, Profesional terhadap Kualitas Audit - Hasbullah Eka Saputra; Cris Kuntadi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Previous research is very important in a scientific research or article. Relevant research serves to strengthen theories and phenomena of relationships or influences between variables. This article is reviewing. Factors that affect the Quality of Internal Audit, namely: Knowledge, Competence, Professional A study of tax accounting literature. The purpose of writing this article is to build a hypothesis of influence between variables to be used in subsequent research This literature review article is: 1). Knowledge Influences Audit.,2) Competence Influences Audit., 3) Professional Influence on Audit.